REALISM AND COMPENSATION: THE RELIGIOUS UNDERSTANDING OF DEATH - John Bowker (Journal of Dharma, 2020)
The Introduction to Problems 01 Suffering in Religions of the World began with two quotations, one from John Donne, the other from Freud. The quotation from Donne ("How much misery is presaged to us, when we come so generally weeping into the world ... ") exemplifies the grim realism about suffering which is prominent in all religions; the quotation from Freud ("It seems not to be true that there is a power in the universe, which watches over the well-being of every individual with parental care...") ex- emplifies the widespread understanding (as much associated with Marx as with Freud) that religions exist and flourish because they offer a supernatural compensation for the natural disasters which overwhelm us with so little apparent equity.